Fitorremediação de efluentes aquícolas e extração de lipídios para a produção de biodiesel utilizando a microalga Chlorella vulgaris - Silva, José William Alves da (2017)
Aquaculture depends on the ecosystems in which it is inserted and it is impossible to grow aquatic organisms without causing environmental changes, but it is possible to significantly reduce impacts on the environment. The bioremediation of effluents using microalgae of high commercial value has already been used in smaller scales and is being introduced, gradually, in systems of more complex crops. The present study had as objective to carry out a prospection for the isolation of microalgae and to use them in the phytoremediation of aquaculture effluents, as well as in the production of biomass and lipid extraction. Two treatments were carried out, with five replicates each, using as culture medium shrimp and pisciculture effluents. Stationary culture was performed in a 5 L volume and was monitored daily by spectrophotometry at 680 nm. Ammonia, nitrite, nitrate and phosphate concentrations were determined at the beginning, middle and end of the cultures. Separation of the cells from the culture medium was performed by chemical flocculation using NaOH2N, after washing, the biomass was oven dried with air renovation at 60 °C for 24 h. The lipid content and the fatty acid profile were analyzed by chromatography. Chlorella vulgaris demonstrated high efficiency in biomass production and nutrient removal in both treatments. The yield (12.00 ± 0.719 g 100 g DW-1) and lipid yield (0.201 ± 0.003 g L-1 day-1) were higher when using the fish effluent. C. vulgaris can be used for the phytoremediation of aquatic effluents and for the production of biomass and lipids. In contrast, the effluent from shrimp farming is the most suitable for recovery of C. vulgaris biomass for the production of biodiesel, since it has a higher content of palmitic acid.